Measuring Parent-Child Relationship (PCR): Development of PC (Adolescent Form) Tool - Sajitha, U.; Parameswari, J (International Journal of Psychosocial Rehabilitation, 2019)
Parent-child relationship has a significant impact in a child’s life that determines the personality characteristics of the children. Parents are the first teachers from whom the children learn values and behaviors to be successful individuals in society. Focusing on the importance of parent-child relationships and considering the research gap in the scales used in the Indian context, it is considered blissful in developing a parent-child relationship scale exclusively from the adolescent perspective. 500 adolescents with the age group ranging from 13 to 19 were taken. Content and face validity were established by collecting opinions from a panel of experts. After conducting the pilot study (first with 500 samples and second with 150 samples), factor analysis was carried out. From a total of 82 items, 30 items were retained after factor analysis with 6 latent variables. Reliability analysis of the data with the second set of 150 samples shows an overall Cronbach alpha of 0.856, which is a relatively high score. A standard parent-child relationship tool from the adolescent perspective is developed. The complete process of scale development and psychometric properties is presented in this article.